Penafsiran Ayat-Ayat Tentang Ghibah, Tajassus, Dan Su’uz Zhan - Muhammad Baihaqi; Siska Heriani; Edy Hasan Hasibuan; Hanifa Sayidatin Nadira; Edi Hermanto (CV. ITTC INDONESIA, 2026)
Social ethics is an important aspect of Islamic teachings that aims to create a harmonious, respectful, and morally sound social life. The Qur'an provides various guidelines regarding behaviors that should be avoided in social interactions, including backbiting, gossiping, and gossiping. These three behaviors have the potential to damage individual honor, weaken social trust, and cause conflict in social life. This study aims to analyze the interpretation of Qur'anic verses related to backbiting, gossiping, and gossiping, identify the moral values ​​contained therein, and examine their relevance in contemporary life. This study uses a qualitative method with a library research type. The main data sources are QS. Al-Hujurat [49]: 12, QS. Yunus [10]: 36, and QS. Al-Fath [48]: 12. The results of the study indicate that backbiting, gossiping, and gossiping are interrelated behaviors rooted in a person's weak self-control and spiritual qualities. The prohibition against these behaviors contains moral values ​​in the form of maintaining human honor, respecting privacy, developing husnuz zhan, applying the principle of tabayyun, and strengthening brotherhood and moral responsibility. These values ​​remain relevant in facing the challenges of social ethics in the digital era. Therefore, understanding and internalizing the teachings of the Qur'an regarding backbiting, gossiping, and gossiping are important in building individual character and creating a harmonious and civilized social life.